The Students Perception of What Makes A Good Teacher (A Descriptive Quantitative Research Conducted at a Junior High School ) - Mulyani, Martina (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
A Teacher is one element influencing the students success in their academic work at school. For that reason, the teacher needs to possess good qualities. The aim of this research is to identify what makes a good teacher in the eye of junior high school students. The research employed quantitative method which utilized numerical data to assess the students perceptions of the teachers’ qualities. 20 students of junior high school were involved in this study. To gain the data the study used questionnaire and interview as the data collection. The findings revealed that a good teacher should possess four different virtues. They are They are technical knowledge, pedagogy skill, interpersonal skill and personality traits with the most wanted qualities are interpersonal skill and personality traits. In the light of the research's findings, it is anticipated that teachers will be able to adopt the personas required by the students.